Burmese Teachers’ Perceptions of Collaborative Instruction and Sources of Student Motivation for Learning Social Studies - Nanmu, Gemma; Orlando González (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
The purpose of this paper is to examine how middle school Social Studies teachers in five government basic education schools at Demoso Township, Kayah State, Myanmar, perceived (a) collaborative instruction, its objectives, and the roles of teachers and students in the collaborative instruction class; and (b) the sources of student motivation for learning Social Studies in relation to intrinsic goal orientation, extrinsic goal orientation, and task value. Data was mainly collected from in-depth individual semi-structured interviews with 10 middle school Social Studies teachers conveniently sampled from the target schools. From the data analysis, which was conducted using the systematic design of grounded theory, it was found that the participants perceived collaborative instruction as having three main objectives: to promote students’ sociocultural, ethical and learning behaviors; to promote students’ self-efficacy for learning Social Studies; and to promote teachers’ self-efficacy for teaching Social Studies; and the roles of teachers and students in the collaborative instruction were found to be in line with such objectives. Moreover, the sources of student motivation for learning Social Studies perceived by the participants were found to be in line with the three sources of motivation for learning identified by the value components of Pintrich and De Groot (1990). Based on these results, recommendations for Social Studies teachers, students and future researchers are provided.